Indexing and inflation - Shanahan, Eileen; Friedman, Milton; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1974)
This book brings together four leading economists in searching discussion of a much talked-about proposal for coping with the burden of inflation.
An AEI round table held on 17 July 1974 at the American Enterprise Institute for Public Policy Research, Washington, D.C.
osc 27/03/2018
Loans
Keywords: Indexation (Economics); Inflation (Finance)